2007
DOI: 10.1001/archinte.167.14.1510
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Adiponectin Levels and Mortality in Elderly Men With and Without Cardiovascular Disease and Heart Failure

Abstract: Background: High adiponectin levels have been associated with reduced cardiovascular risk but have been shown to predict mortality in those at high risk for vascular disease. We examined the relationship between adiponectin levels and mortality in older men with and without diagnosed cardiovascular disease (CVD) and heart failure. Methods: Prospective study of 4046 men aged 60 to 79 years drawn from general practices in 24 British towns and followed up for a mean of 6 years, during which 734 deaths occurred. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
144
0
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(173 citation statements)
references
References 44 publications
20
144
0
9
Order By: Relevance
“…Interventions that enhance adiponectin secretion or action may therefore have potential for treatment of metabolic and vascular disease, although the clinical evidence for adiponectin being protective against cardiovascular disease is conflicting. 38 At any rate circulating adiponectin level is a strong risk marker for MetS independent of measures of adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that enhance adiponectin secretion or action may therefore have potential for treatment of metabolic and vascular disease, although the clinical evidence for adiponectin being protective against cardiovascular disease is conflicting. 38 At any rate circulating adiponectin level is a strong risk marker for MetS independent of measures of adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that in elderly men, high adiponectin levels are associated with increased all-cause and cardiovascular disease mortality (22). However, subgroup analyses in individuals aged Ͼ60 years revealed similar associations of adiponectin receptor gene expression with insulin resistance and obesity compared with younger subjects.…”
Section: Statistical Analysesmentioning
confidence: 95%
“…Another possible explanation for the obesity paradox directly involves the functions of adipose tissue (11,66) . Adipose tissue produces leptin which experimental studies suggest may have protective effects in HF (71) and adiponectin is decreased in obesity; lower concentrations of adiponectin have been associated with lower mortality in patients with CHD or HF (72)(73)(74) .…”
Section: The Obesity Paradox In Those With Chdmentioning
confidence: 99%